2001
DOI: 10.1105/tpc.13.1.89
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation of the Mitochondrial ABC Transporter Sta1 Leads to Dwarfism and Chlorosis in the Arabidopsis Mutant starik

Abstract: A mutation in the Arabidopsis gene STARIK leads to dwarfism and chlorosis of plants with an altered morphology of leaf and cell nuclei. We show that the STARIK gene encodes the mitochondrial ABC transporter Sta1 that belongs to a subfamily of Arabidopsis half-ABC transporters. The severity of the starik phenotype is suppressed by the ectopic expression of the STA2 homolog; thus, Sta1 function is partially redundant. Sta1 supports the maturation of cytosolic Fe/S protein in ⌬ atm1 yeast, substituting for the AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
131
0
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(135 citation statements)
references
References 38 publications
3
131
0
1
Order By: Relevance
“…This phenomenon has been studied in yeast, animal cell cultures, and plants (for review, see Butow and Avadhani, 2004;Rhoads and Vanlerberghe, 2004). There are several interesting examples in which nuclear gene expression was altered in plants by mitochondrial dysfunction caused by nuclear mutation or transgenic expression of mitochondrial proteins (Kushnir et al, 2001;Gó mez-Casati et al, 2002;Rhoads et al, 2005). Although not directly demonstrated in these examples, there is evidence for the importance of mtROS in plant MRR.…”
Section: Mtros As Signals Affecting Nuclear Gene Expression and Cell mentioning
confidence: 99%
“…This phenomenon has been studied in yeast, animal cell cultures, and plants (for review, see Butow and Avadhani, 2004;Rhoads and Vanlerberghe, 2004). There are several interesting examples in which nuclear gene expression was altered in plants by mitochondrial dysfunction caused by nuclear mutation or transgenic expression of mitochondrial proteins (Kushnir et al, 2001;Gó mez-Casati et al, 2002;Rhoads et al, 2005). Although not directly demonstrated in these examples, there is evidence for the importance of mtROS in plant MRR.…”
Section: Mtros As Signals Affecting Nuclear Gene Expression and Cell mentioning
confidence: 99%
“…In plants, ABC transporters have been localized to the tonoplast, mitochondria, chloroplasts, and plasma membrane (Kushnir et al, 2001;Moller et al, 2001;Goodman et al, 2004;Pighin et al, 2004). Recently, proteomic studies of different organelles have placed PEN3 in the plasma membrane, mitochondria, and chloroplasts (Brugiere et al, 2004;Kleffmann et al, 2004;Nü hse et al, 2004).…”
Section: Localization Of Pen3 To Penetration Sites After Pathogen Attackmentioning
confidence: 99%
“…However, for consistency with previous publications, we have adhered to the ATM gene symbols in this paper.) Expression of GFP fusions showed that all three ATM proteins localized to mitochondria (Kushnir et al, 2001;Chen et al, 2007). Arabidopsis ATM3 could functionally complement the yeast atm1 phenotype (Kushnir et al, 2001;Chen et al, 2007), whereas Arabidopsis ATM1 complemented poorly and ATM2 expression was toxic in yeast (Chen et al, 2007).…”
mentioning
confidence: 99%
“…Plant cytosol contains homologs of the cytosolic Fe-S assembly proteins that have recently been identified in yeast (Lill and Mü hlenhoff, 2008), including the scaffold protein AtNBP35 (Bych et al, 2008;Kohbushi et al, 2009) and the hydrogenase-like AtNAR1 (Cavazza et al, 2008). It is thought that cytosolic Fe-S cluster assembly is dependent on at least one of the organelles, because the Cys desulfurases that generate sulfur for Fe-S clusters, CpNifS and NFS1, are strictly localized in the plastids and mitochondria, respectively (Kushnir et al, 2001;Frazzon et al, 2007;Van Hoewyk et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation